Occupational gender segregation in an equilibrium search model - Emiko Usui (IZA Journal of Labor Economics, 2015)
This paper develops an equilibrium search model to explain gender asymmetry in occupational distribution. Workers' utility depends on salary and working hours, and women have a greater aversion to longer working hours than men. Simulations indicate that women crowd into shorter-hour, lower-paying jobs than men. If employers discriminate against women, offers are tailored more toward the working-hour preferences of men by requiring longer working hours. Similarly, if women have a disutility factor in their utility toward positions with a higher proportion of men, fewer women work at these jobs. In both cases, gender segregation is reinforced.
Keywords: E24; J16; J64; J71; 330; Equilibrium search; Gender preferences; Employer discrimination; Employee discrimination